Pedo-environmental determination of olive oil quality: a case study - Leone A.P.; D'Andria R.; Morelli G.; Fragnito F.; Purificato S.; Volpe M.G.; Nazzaro M.; Buonduonno A. (Present and future of the Mediterranean olive sector, 2013)
This paper reports the preliminary results of a study regarding the influence of different pedo-environments of the Benevento province on the composition of olive oil from the 'Ortice' cultivar and the specific relationships among individual soil properties and olive oil compounds. Multivariate statistical analyses (Principal Component Analysis, PCA and Partial Least Squares Regression PLSR) were used for the investigation. Results from PCA showed a clear tendency of olive oil samples from the different pedo-environment to cluster, although the distance among clusters was not relevant. Results from PLSR showed some interesting relationships among several soil properties and olive oil compounds. These relationships were relevant when PLSR was applied separately to samples from individual pedo-environments, while it was less relevant when applied to the data set as a whole. Further investigations will enlarge the data set, also including other cultivars.
International Seminar: Present and Future of the Mediterranean Olive Sector, 2012/11/26-28, Zaragoza (Spain)